DNA-Ploidy in Advanced Gastric Carcinoma is Less Heterogeneous than in Early Gastric Cancer - Maria‐Chiara Osterheld; Liette Caron; Mireille Demierre; Ricardo Laurini; F. T. Bosman (Cellular Oncology)
This analysis of DNA‐ploidy heterogeneity in advanced gastric carcinomas is consistent with the hypothesis of the emergence of a single aneuploid cell clone as a crucial mechanism in the progression from early gastric carcinoma to advanced gastric cancer. The prognostic value of DNA‐ploidy in gastric cancers has been a matter of controversy. Tumour DNA‐ploidy heterogeneity, the presence within the same tumour of multiple stemlines differing in DNA content, has been described in various tumours including gastric cancers. The occurrence of such heterogeneity has been accepted as an explanation for the divergent DNA‐ploidy results in this type of tumours. A previous study of early gastric cancers suggested that in pure diploid superficial carcinomas, genetic instability might lead to a cell clone which has undergone a ploidy shift and is more aggressive. If so, this would initially result in DNA‐ploidy heterogeneity. Proliferative dominance of the aneuploid clone could eventually evolve to a homogeneous aneuploid tumour. In order to test this hypothesis, we studied DNA‐aneuploidy and DNA‐ploidy heterogeneity in advanced gastric carcinomas. We performed DNA cytophotometry on multiple samples collected from 16 advanced gastric carcinomas and found 15 DNA‐aneuploid tumours (94%) and one diploid tumour. Multiple DNA‐stemlines were found in 4 cases (26%). Analysis of proliferative activity performed on the same samples revealed higher proliferation rate in DNA‐ploidy homogeneous tumours than in aneuploid heterogeneous tumours. Heterogeneous tumours did not overexpress p53. These results confirm that DNA‐aneuploidy is frequent in advanced gastric cancer and demonstrate that a majority of these aneuploid tumours are not DNA‐ploidy heterogeneous. Furthermore, the higher proliferative activity in homogeneous‐aneuploid carcinomas and their more frequent overexpression of p53 support the hypothesis that in gastric cancer tumour progression implies the development of a dominant and more aggressive (higher proliferative activity, p53 overexpression) aneuploid cell clone.